A single nucleotide polymorphism possibly associated with fat deposition is methylated in the bovine TFAM promoter - Tanja KUNEJ; Zeping WANG; Jennifer J. MICHAL; Peter DOVČ; Nancy S. MAGNUSON; Zhihua JIANG (Acta Agriculturae Slovenica)
Mitochondrial transcription factor A (TFAM) is a nuclear-encoded mitochondrial protein that plays an important role in energy metabolism and is a candidate gene for fat deposition in cattle and human. In the present study, we characterized the methylation status of bovine TFAM promoter flanking the single nucleotide polymorphism (SNP) rs42159487C>T, previously reported to affect fat deposition. Our results showed that the cytosine at this SNP position is methylated and therefore results in gain/loss of the functional CpG locus (5mC>T). Promoter constructs developed based on three TFAM SNPs showed that the C/C/C haplotype associated with fat deposition in beef cattle had lower promoter function/activity than A/T/T haplotype. Our results imply that genetic variability underlying gain/loss of the CpG sites in the nuclear-encoded mitochondrial proteins might be good candidate loci for fat deposition phenotypes.